2004
DOI: 10.1126/science.1096378
|View full text |Cite
|
Sign up to set email alerts
|

CD8 + T Cell Cross-Priming via Transfer of Proteasome Substrates

Abstract: "Cross-priming" describes the activation of naïve CD8+ T cells by professional antigen-presenting cells that have acquired viral or tumor antigens from "donor" cells. Antigen transfer is believed to be mediated by donor cell-derived molecular chaperones bearing short peptide ligands generated by proteasome degradation of protein antigens. We show here that cross-priming is based on the transfer of proteasome substrates rather than peptides. These findings are potentially important for the rational design of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
211
5

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(235 citation statements)
references
References 21 publications
19
211
5
Order By: Relevance
“…Both HSP70 and HSP90 can facilitate the presentation of antigenic peptides on MHC class I molecules, but HSC70 can facilitate TAA processing and presentation on MHC class II molecules (52). Recent studies have shown that crosspriming is based on the transfer of proteasome substrates that are transcriptionally up-regulated by heat treatment in human cells (53,54). This concept offers additional effects by which heat treatment might enhance Ag processing and presentation in MHC class I and II molecules on the surfaces of FCs.…”
Section: Discussionmentioning
confidence: 99%
“…Both HSP70 and HSP90 can facilitate the presentation of antigenic peptides on MHC class I molecules, but HSC70 can facilitate TAA processing and presentation on MHC class II molecules (52). Recent studies have shown that crosspriming is based on the transfer of proteasome substrates that are transcriptionally up-regulated by heat treatment in human cells (53,54). This concept offers additional effects by which heat treatment might enhance Ag processing and presentation in MHC class I and II molecules on the surfaces of FCs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, much of what is known about the cross-presentation of virus antigens is derived from studies relying on antigen donor cells (ADC) transfected with a single virus protein [7][8][9][10]. The ability of antigens to escape cytosolic degradation in ADC is important during cross-presentation [7,[11][12][13]. Interestingly, it appears that the capacity of an epitope to access cross-priming may support its immunodominance when considering the overall hierarchy [8,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-priming is a crucial pathway of exogenous antigen presentation on the HLA class I molecules by APCs, enabling antiviral or antitumour responses (den Haan et al 2000;Sigal et al 1999). It has been shown that intact proteins or non-chaperoned proteasome products can be a source of antigens used for cross-presentation (Norbury et al 2004;Serna et al 2003;Shen and Rock 2004). However, these molecules were shown not to be as effective in cross-priming as peptides chaperoned by HSPs (Binder et al 2001;Binder and Srivastava 2005).…”
Section: Introductionmentioning
confidence: 99%